Fitness instructors' perception of importance of particular elements for effectively conducted program - Špehar, N.; Fučkar Reichel, K.; Gošnik, Jelka (2007)
The goal of this study was to determine importance of particular exercise elements for effective fitness class from the viewpoint of an instructor. Our survey included 120 fitness instructors in Croatia with average age of 29.3 years and average career of 6.3 years. Factor analysis with a component model in conjunction with GK criterion for truncation of extraction factors and varimax transformation of basic solution was applied to examine dimensionality of instruments – importance of effective fitness class. We have determined four latent dimensions that can explain 58.8% of total variance. Data were processed with SPSS statistic software. Well-trained and experienced fitness instructor is critical for a program of exercises to achieve full potential and effectiveness. Instructors should be good teachers as well as good demonstrators and experts reflecting competency. Appropriate and quality education of instructors enables gaining adequate level of knowledge and experience for planning and conducting effective training and methods that can truly benefit all the participants in a fitness class.
ENG